Neuroglobin is capable of self-oxidation of methionine64 introduced at the heme axial position. Issue 32 (20th July 2018) - Liu, Hai-Xiao; Li, Lianzhi; He, Bo; Gao, Shu-Qin; Wen, Ge-Bo; Lin, Ying-Wu
Abstract : The H64M neuroglobin mutant adopts a high-spin heme state and is capable of self-oxidation of the heme axial Met64, producing both methionine sulfoxide (SO-Met) and sulfone (SO2 -Met), which represents the structure and function of cytochrome c in a non-native state. Abstract : Neuroglobin (Ngb), with its physiological role not fully understood, was found to be capable of self-oxidation of methionine64 introduced at the heme axial position (H64M Ngb), adopting a high-spin heme state and producing both methionine sulfoxide (SO-Met) and sulfone (SO2 -Met), which represents the structure and function of cytochrome c in a non-native state.